(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The digital revolution has significantly changed the global economic landscape, ushering in the era of the digital economy. The purpose of this article is to provide a comprehensive analysis of the development of the digital economy in both developing and developed countries, considering key trends, challenges and opportunities. In this article, countries such as Singapore and Thailand are taken as examples. We analyzed how different the methods of developing the digital economy are as representatives of countries with developed and developing economies.